대구지역에서 민주시민교육의 현실과 과제 - 최병덕(Choi, Byung-Deok); 채장수(Chae JangSoo) (한국학논집, 2017)
본 연구는 대구지역 민주시민교육의 현실을 통계자료와 심층면접조사를 통해 분석하고 민주시민교육을 활성화시킬 방안을 모색한다. 2016년도 평생교육통계에 따르면 대구지역 평생교육기관수는 153개, 프로그램의 수는 7,655개, 학습자수는 248,787명이다. 하지만, 운영하고 있는 프로그램은 대부분 문화예술 프로그램과 인문교양 프로그램으로 시민성 향상을 위한 시민참여 프로그램은 매우 저조한 편이다. 대구지역의 시민단체들은 지역 특유의 보수성과 지역관료들의 경직성, 시민의식의 미약함 속에서도 여러 층위의 민주시민교육 프로그램을 운영하고 있다. 그러나 그 내용은 특정분야에 한정되어 있고, 진행 방식은 주로 일방적 강연 중심이다. 또한 대부분 즉각적이고 일회적으로 진행되어 체계성이나 연속성을 가지지 못하고 있다. 이러한 대구지역 민주시민교육의 상황을 ‘풍요 속의 빈곤’이라고 표현할 수 있다. 시민을 대상으로 하는 교육은 풍부하지만 시민성과 공공성을 향상시키는 민주시민교육은 빈곤하기 때문이다. 본 연구는 대구지역 민주시민교육의 빈곤한 상황을 극복하기 위해 먼저 민주시민교육의 양적 팽창이 필요함을 지적한다. 시민들이 민주시민교육을 일상적이고 폭넓게 경험할 수 있는 다양한 기회를 제공하는 것이 우선 필요하기 때문이다. 그리고 대구 민주시민교육의 활성화를 위한 과제를 제도적 측면과 내용적 측면으로 나누어 제시한다. 제도적 측면에서는 ‘조례 제정’과 ‘기금 조성’, 그리고 ‘기구 설립’ 및 ‘협력시스템 구축’을 제시하고, 내용적 측면에서는 ‘책임자 육성’과 ‘프로그램 개발’, 그리고 ‘교육활동 지원’을 제시한다. By way of analysis of statistical data and in-depth interview, this study aims to analyze the reality of democratic citizenship education of Daegu area, and to suggest ways to revitalize it. According to 2016 lifelong education statistics, there are 153 lifelong education institutions, 7,655 programs, and 248,787 students in Daegu area. However, most of the programs are centered on cultural art and liberal art programs. Thus, programs for citizen participation are very few. In the midst of local tendency of conservatism, rigidness of local government officials, and weak citizenship, civic groups of Daegu area are operating various levels of democratic citizenship education programs. But the contents of education are limited to specific subjects, and the way of education is centered on one-sided lectures. In addition, most of them have not been systematic or continuous since they are being performed only once and instantly. So the situation of democratic citizenship education in Daegu area can be described as ‘poverty in abundance’. It is due to the fact that though education programs for citizens are abundant, the educations for citizens for the growth of citizenship and publicness are poor. In order to overcome the poor situation of Daegu area’s democratic citizenship education, this study, most of all, points out the necessity to expand the number of democratic citizenship education. For it is necessary to provide various opportunities for citizens to experience democratic citizenship education everyday and widely. Also, this study suggests ways to revitalize Daegu area’s democratic citizenship education from two separate aspects. One is institutional aspect, and the other is aspect of contents. From the institutional aspects, we have dealt with the problems of ‘regulations’, ‘fund’, and ‘organizations’ and ‘cooperation system’. From the aspects of contents, we have dealt with the problems of ‘nurturing supervisor and coordinator’, ‘program development’, and ‘education support’. KCI Citation Count: 0